Generative AI for Enhancing Accessibility and Inclusion in Higher Education: A Systematic Review - José Alejandro Jaime-Vargas (HighTech and Innovation Journal)
This study reviews existing literature on generative artificial intelligence (AI) and its accessibility for students with visual, hearing, and motor disabilities in higher education. The objective is to identify gaps in the implementation of inclusive education practices. The PRISMA protocol guided the review process, and the Scopus and Web of Science databases were selected for their recognized academic rigor and comprehensive coverage. The first phase involved the review of 54 articles in English from 2023 to 2024. The selection process involved prioritizing articles based on empirical scientific studies on AI applications for students with disabilities, and discarding articles that did not meet the criteria. Ultimately, only five articles were selected. The findings reveal a significant research gap regarding the role of generative AI in supporting these students. Notably, the selected articles tend to focus more on sensory disabilities than on motor disabilities. This study is pioneering in pointing out the lack of research on motor disabilities during the analyzed period, a key aspect of AI in higher education. These findings underscore the necessity of further research that aligns with the UN 2030 Agenda, specifically Goals 4 (Quality Education) and 10 (Reduced Inequalities), promoting the development of AI tools that foster equal opportunities and inclusive education.